Differences in Practitioner Experience, Practice Type, and Profession in Attitudes Toward Growing Contact Lens Practice. Issue 9 (September 2022) - Thite, Nilesh; Desiato, Alfredo; Shinde, Lakshmi; Wolffsohm, James S; Naroo, Shehzad A.; Santodomingo Rubido, Jacinto; Cho, Pauline; Jones, Debbie; Villa-Collar, Cesar; Carrillo, Guillermo; Chan, Osbert; Wang, Haiying; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To investigate eye care practitioners' attitudes and perceptions toward potential interventions that can enhance contact lens (CL) practice across the world, and how this is influenced by their practice setting. Methods: A self-administered, anonymized survey was constructed in English and then forward and backward translated into six more languages. The survey was distributed online via social media platforms and mailing lists involving reputed international professional bodies. Results: In total, 2, 222 responses from 27 countries with sufficient responses were analyzed (53% females, median age- 37 years). Most of the respondents were optometrists (81.9%) and 47.6% were from stand-alone/independent practices. Median working experience in CL prescribing was 11.0 years (IQR: 18.0, 4–22 years). Over two-third of them declared themselves to be very hopeful (22.9%) or hopeful (45.1%) about the future of their CL practice. Among the potential interventions proposed, continuous update of knowledge and skills and competently managing CL-related complications were rated the most important (median score: 9/10 for each). Practitioners working in national/regional retail chains expressed higher proactivity in recommending CLs (9/10) than those in local chains, hospitals, and universities (for all 8/10, P <0.05). National differences were also identified in eye care practitioner attitudes and perceptions ( P <0.05). Conclusions: The study provided important information to delineate a variety of elements characterizing CL practice across the world. These insights can serve as a basis to design strategies at national and international levels.